Meaning in Life in College Students: Implications for College Counselors. Issue 1 (April 2017) - Trevisan, Dominic A.; Bass, Ellyn; Powell, Kevin; Eckerd, Lizabeth M.
Abstract : The authors examined the relationship between meaning in life and college adjustment in a sample of 96 college students. In line with previous research on meaning in life and positive psychosocial functioning measures, presence of meaning was positively correlated with adjustment, whereas searching for meaning was negatively correlated with adjustment. However, the degree to which students were actively searching for meaning moderated the relationship between presence of meaning and adjustment. Recommendations for college counseling services are discussed.